Molecular, morphological, and biogeographic perspectives on the classification of Acrobolboideae (Acrobolbaceae, Marchantiophyta) - Briscoe, Laura R. E.; Zerega, Nyree J. C.; Lumbsch, H. Thorsten; Stech, Michael; Kraichak, Ekaphan; Konrat, Matthew J. Von; Engel, John J.; Wickett, Norman J. (Phytotaxa, 2017)
The liverwort subfamily Acrobolboideae has historically contained the three genera: Acrobolbus, Marspidium, and Tylimanthus. Generic delimitations in this subfamily have been historically inferred from morphological characters, specifically the location of gametangia. Taxonomists have had difficulty separating the genera, with some combining Tylimanthus and Acrobolbus, whereas others merged Marsupidium and Tylimanthus. We used five chloroplast loci to reconstruct a phylogeny of the group, revealing all three genera are polyphyletic as currently described. An assessment of key morphological characters used to separate genera in the subfamily resulted in several observations: characters used to circumscribe Acrobolbus were homoplasious; characters used to circumscribe each genus (e.g., the placement of female reproductive organs) do not reflect phylogenetic relationships; and the evolutionary trajectories of some characters (i.e., the number of antheridia, male reproductive organs, per male bract) correspond directly with previous evolutionary hypotheses for the family, but do not follow historical taxonomic inferences. Irrespective of generic concepts, several well–supported clades within the phylogeny have a strong biogeographic structure. Using these lines of evidence, we recognize Acrobolbus as a single genus in Acrobolboideae.